Master track of ALKOR cruise AL633 in 1 sec resolution (zipped, 64 MB) - Bange, Hermann W; Stoltenberg, Ina (GEOMAR - Helmholtz Centre for Ocean Research Kiel, 2025)
Raw data acquired by position sensors on board RV Alkor during expedition AL633 were processed to receive a validated master track which can be used as reference of further expedition data. During AL633 data from the Seapath 330 system, the Furuno GP-170 and the Furuno GP-150 GPS receivers were used to calculate the mastertrack. Data were downloaded from DAVIS SHIP data base (http://dship.bsh.de) with a resolution of 1 sec. Processing and evaluation of the data is outlined in the data processing report. Processed data are provided as a master track with 1 sec resolution derived from the position sensors' data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.
Keywords: 1 sec resolution